Епидемиолошко клиничка проценка на вистинскиот хоспитален морталитет од миокарден инфаркт - Петковиќ, Наташа (Медицински факултет, УКИМ, Скопје, 2019)
Introduction: Mortality from contagious diseases has declined and there is increase in incidence of cronical diseases including cardiovascular diseases . This has important impact on the trajectory of the health systems of 21th century. Altough there is a lot of knowledge about the CVD especially AMI and CVD the population data are problematical. That’s why WHO started the WHO Multinational MONItoring of Trends and determinants in CArdiovacular disease (MONICA) Project for the period of 10 and more years. This project is containing high quality data and well described high quality metods. Motives: until now in our country there is no paperjk about the accuracy of the death certificates from the CVS and the main focus on early intrahospital motraliti from AMI . This investigatin is the first one in our country and it’s to be expected to obtain our own accurate data aboiut mortality from CVS and AMI and to compaire them with the results from the other countries. Aims: the study has primary aim to reveal the accuracy of the death certificates primary reason for f death is CVD or AMI. Matherials and methods: The research is quantitative analithyc study –cross sectional study implemented from January 2015 to September 2016. The death certificates containing main ICD codes I10- i50 from the City general hospital September the 8th Skopje, Clinical hospital Bitola, Clinical hospital Stip, Clinical hospital Tetovo, General hospital Kumanovo, General hospital Prilep . The selection of the analyzed death certificates and hospilata l data was according to determined inclusion and exclusion criteria. Results: There is inconsistency in the filling of the Deatth Certificates with the inscribed ICD (I10 - I50) as the main cause of death. The hospital medical documentation for the patients who died in the first 24 hours is incomplete. There is a difference of 10% between the contents of the ICD inscription (I10) - I50) as the primary cause of death and appropriate hospital medical documentation. The number of AMI patients dying in hospital facilities is significantly higher than that reported in the LIPS.
Epidemiological and clinical assesment of the real hospital mortality from acute myocardial infarction
Докторска дисертација одбранета во 2019 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Весна Велиќ Стефановска.
Keywords: accuracy death certificates, early hospital AMI mortality, WHO MONICA project